Lacustrine, wastewater, interstitial and fluvial water quality in the Southern Lake Baikal region. (10th December 2021) - Malnik, Valerii V.; Yamamuro, Masumi; Tomberg, Irina V.; Molozhnikova, Elena V.; Bukin, Yuri S.; Timoshkin, Oleg A.
Abstract: The coastal area of the southern Lake Baikal with the population over 35, 000 people remains an attractive spot for both tourists and local residents. Despite high anthropogenic impact, a detailed assessment of water quality in this area has not been performed so far. Here, we performed a comprehensive evaluation of the quality of the surface, bottom and interstitial water in rivers, lacustrine water and wastewater in the southern Lake Baikal region. We analyzed 37 samples for the presence of fecal enterococci, Escherichia coli and assessed their hydrochemical parameters: concentrations of nutrients (nitrate-N, nitrite-N, ammonium-N and phosphate-P), dissolved oxygen and amount of ions (HCO3 − + SO4 2− + Cl − + Ca 2+ + Mg 2+ + Na + + K + ). In addition, the temperature, pH and electrical conductivity were also measured. We found that multiple areas around South Baikal suffer from microbiological and hydrochemical pollution. We conclude that ecological situation in this area requires immediate attention from local authorities, more efficient wastewater management systems should be constructed in the settlements. We also conclude that interstitial waters from the lake's splash zone represent an effective and sensitive indicator of sanitary-microbiological and hydrochemical pollution and their analysis can be included in the standard protocol of water quality assessment for all types of water bodies. HIGHLIGHTS: Water quality analysis of the South Lake Baikal area is presented. Concentration of fecal bacteria in the rivers near settlements is significantly higher than that of the protected areas. Concentration of nutrients in the interstitial water in Listvyanka settlement is significantly higher than that of lake water. The splash zone represents an effective indicator of pollution in the coastal areas of Lake Baikal. Graphical Abstract